New conception of cancer prevention strategy in the Odesa region: modern program and personificated approach - Rybin, A.; Kuznetsova, O. (Journal of Education, Health and Sport, 2025)
The authors analyse the state of cancer care in Ukraine and its future trends, taking into account the impact of the war. The paper highlights and analyses the current aspects of the problem of early diagnosis of cancer against the background of reforming medicine in general and the oncological service in particular. The main problems of the oncological service in the region and the state of the organisation of diagnosis of malignant pathology by family doctors are shown. The experience of solving the main problems of the lack of high-quality oncological diagnostics, oncological prevention and interaction between primary and other levels of oncological care at the level of Odesa is presented, and a modern approach to improving the state of the oncological service in the region is proposed. The main vectors of development of the oncological service in the framework of healthcare reform in Ukraine are described.